What else is in your supplement? A review of the effectiveness of the supportive ingredients in multi-ingredient performance supplements to improve strength, power, and recovery - Allman, B. R.; Kreipke, V. C.; Ormsbee, M. J. (Strength and Conditioning Journal, 2015)
This review summarizes the empirical research of the effectiveness, safety, and dosages of the lesser-known, but commonly added, supportive ingredients in multi-ingredient performance supplements (mips). Primary ingredients that are well known and previously reviewed (i.e., caffeine, creatine, beta-alanine) are excluded from this review. The improvements reported are commonly mediated by secondary mechanisms such as improved blood flow, protein balance, metabolism, and antioxidant status. Overwhelming evidence exists suggesting that the supportive ingredients in mips are safe to use; however, the amount present in most mips is likely too small to elicit strength, power, or recovery responses.